Cardiometabolic Health After Pediatric Cancer Treatment: Adolescents Are More Affected than Children. (13th August 2022) - Bélanger, Véronique; Napartuk, Mélanie; Bouchard, Isabelle; Meloche, Caroline; Curnier, Daniel; Sultan, Serge; Laverdière, Caroline; Sinnett, Daniel; Marcil, Valérie
Abstract: This cross-sectional study aimed at comparing the cardiometabolic (CM) health of children and adolescents and identifying factors associated with CM complications shortly after cancer treatment. Cancer-related characteristics, blood pressure (BP), anthropometry, and biochemical parameters were collected in 80 patients (56.3% female, mean age: 11.8 years; range: 4.5 − 21.0) a mean of 1.4 years following therapy completion. Compared to children, adolescents had higher mean z -score of insulin (–0.47 vs. 0.20; P = 0.01), HOMA-IR (–0.40 vs. 0.25; P = 0.02), waist-to-height ratio (0.36 vs. 0.84; P = 0.01), subscapular skinfold thickness (–0.19 vs. 0.47; P = 0.02), total body fat (–1.43 vs. 0.26; P < 0.01), and lower mean z -score of HDL-C (0.07 vs. –0.53; P < 0.01). Adolescents were more likely to have high BP (42% vs. 15%; P < 0.01), dyslipidemia (64% vs. 15%; P < 0.001), and cumulating ≥ 2 CM complications (42% vs. 2%; P < 0.001) than children. Adiposity indices ( z -scores) were associated with high BP [odds ratio (OR) ranging from 2.11 to 4.09] and dyslipidemia (OR ranging from 2.06 to 4.34). These results suggest that adolescents have a worse CM profile than children shortly after therapy and that adiposity parameters are associated with CM complications, highliting the importance to develop intervention strategies targeting this population.